Effects of Dietary Energy Level on Performance, Plasma Parameters, and Central AMPK Levels in Stressed Broilers - Hu, Xiyi; Li, Xianlei; Xiao, Chuanpi; Kong, Linglian; Zhu, Qidong; Song, Zhigang (Frontiers in Veterinary Science, 2021)
This study aimed to characterize the effects of diets with different energy levels on the growth performance, plasma parameters, and central AMPK signaling pathway in broilers under dexamethasone (DEX)-induced stress. A total of 216 1-day-old male broiler chickens were allocated to groups fed with high (HED), National Research Council-recommended (CON), or low (LED) energy diets. At 10 days old, chickens were treated with or without dexamethasone (DEX, 2 mg/kg body weight) for three consecutive days. HED increased broiler average daily gain (ADG) at 10 days old, compared with the LED (P < 0.05), while average daily feed intake (ADFI) and feed conversion rate (FCR) decreased as the dietary energy level increased (P < 0.05). Chickens fed a HED had higher total protein (TP) content, albumin (ALB), glucose (GLU), total cholesterol (TCHO), high-density lipoprotein (HDL) cholesterol, and low-density lipoprotein (LDL) cholesterol, compared with the CON group (P < 0.05). At 13 days old, DEX decreased ADG and increased FCR in broilers fed with different energy diets (P < 0.05). The DEX-HED group had a higher ADFI than non-DEX treated HED group chickens. In addition, TP, ALB, TG, TCHO, HDL, and LDL content levels in the DEX group were higher than those in the control group (P < 0.05). The UA content of the LED group was higher than that of the HED group (P < 0.05). Further, gene expression levels of liver kinase B1, AMP-activated protein kinase α1, neuropeptide Y, and GC receptor in the hypothalamus were increased in chickens treated with DEX (P < 0.05). There was a trend toward interaction between plasma TCHO and hypothalamic LKB1 expression (0.05 < P < 0.1). In conclusion, this study suggests that HED improves growth performance, plasma glucose and total cholesterol at 10 days old broilers, but had no significant effect on performance, plasma parameters, and central AMPK in stressed broilers.